Islands in the mud: The South Texas banks provide crucial mesophotic habitat for coral communities - Bollinger, Maria; Macartney, Keir J.; Easton, Erin E.; Hicks, David W. (Frontiers in Marine Science, 2022)
On the continental shelf off the coast of South Texas lie a series of natural hard-bottom structures (rocky outcrops and relic coral-algal reefs) known as the South Texas Banks (STB), which provide critical habitat for benthic organisms and pelagic fish. The depth of the banks, a persistent nepheloid layer, and strong currents have resulted in few studies that provide quantitative biodiversity data on the STB. Using a remotely operated vehicle (ROV), video surveys were conducted to quantitatively describe the mesophotic coral communities and assess habitat suitability of five STB: North Hospital, Hospital, Southern, Big Adam, and Mysterious Banks. Each of these STB have significantly different benthic communites, with coral communities composed primarily of antipatharians and octocorals. Big Adam Bank had the lowest biodiversity and the least coral cover. Mysterious Bank had abundant antipatharians, specifically Stichopathes spp., but low biodiversity overall. Hospital Bank had low coral diversity that was offset by high diversity in sponges and other invertebrate species. North Hospital and Southern Banks had abundant and diverse populations of coral species, including scleractinians, and other benthic invertebrates. These data indicate that the STB are crucial islands of biodiversity in an area with few suitable areas for coral reef species. In addition, predictive modelling of habitat suitability provided valuable estimates on the potential distribution of key benthic community members, such as scleractinians and antipatharians, throughout the entire area of the five banks assessed.